On the magnetic field through the Upper Centaurus-Lupus super bubble in the vicinity of the Southern Coalsack - Bhat, Ramesh; Andersson, B. (Institute of Physics Publishing, 2011)
The Southern Coalsack is located in the interior of the Upper Centaurus-Lupus (UCL) super bubble and shows many traits that point to a much more energetic environment than might be expected from a dark, starless molecular cloud. A hot, X-ray emitting envelope surrounds the cloud, it has a very strong internal magnetic field, and its darkest core seems to be on astronomical timescales 'just about' to start forming stars. In order to probe the magnetic environment of the cloud and to compare with the optical/near-infrared polarimetry-based field estimates for the cloud, we have acquired Faraday rotation measurements toward the pulsar PSR J1210-6550, probing the magnetic field in the vicinity of the cloud, and a comparison target, PSR J1435-5954, at a similar line-of-sight distance but several degrees from the cloud. Both lines of sight hence primarily probe the UCL super bubble. The earlier estimates of the magnetic field inside the Coalsack, using the Chandrasekhar-Fermi method on optical and near-infrared polarimetry, yield B ? = 64-93 µG. However, even though PSR J1210-6550 is located only ~30 arcmin from the (CO) edge of the cloud, the measured field strength is only B ? = -1.1±0.2 µG. While thus yielding a very high field contrast to the cloud we argue that this might be understood as due to the effects on the cloud by the super bubble. © 2011. The American Astronomical Society. All rights reserved.